New method for quantifying power during wheelchair sports propulsion in the field - Deves, M.; Marsan, T.; Faupin, A.; Watier, B. (Sports Biomechanics, 2025)
The importance of accelerating from a standstill is crucial in dynamic wheelchair sports, as it is closely tied to the ability to generate and apply significant power and net horizontal propulsion force. Assessing and quantifying para-athletes` physical capabilities could enhance training to performance transition. This study aimed to propose a field method for quantifying total wheelchair propulsion forces and output power, while exploring the usability of the 1080 Motion Sprint. Five para-athletes from the national French wheelchair racing team and seven wheelchair tennis players from the national French team participated. Unloaded and resisted sprints of 50 m and 20 m were performed. Mono-exponential velocity function was deduced using photocells, IMUs and the 1080 Motion Sprint velocity-time raw data. Net horizontal propulsion force was estimated from Newton`s second law and considered the loads applied by the 1080 Motion Sprint, rolling resistance and aerodynamic drag. While no significant difference was observed between conditions for theoretical maximal force and maximum power developed, variations were evident in estimated power output and mechanical variables from force-velocity relationships, contingent on the athlete`s classification and sport speciality. The developed protocol can be used by trainers to assess physical capacities during training sessions, guiding subsequent training.